Buoy-based detection of low-energy cosmic-ray neutrons to monitor the influence of atmospheric, geomagnetic, and heliospheric effects - Schrön, Martin; Rasche, Daniel; Weimar, Jannis; Köhli, Markus; Herbst, Konstantin; Boehrer, Bertram; Hertle, Lasse; Kögler, Simon; Zacharias, Steffen (Earth and Space Science, 2024)
Cosmic radiation on Earth responds to heliospheric, geomagnetic, atmospheric, and lithospheric changes. In order to use its signal for soil hydrological monitoring, the signal of thermal and epithermal neutron detectors needs to be corrected for external influencing factors. However, theories about the neutron response to soil water, air pressure, air humidity, and incoming cosmic radiation are still under debate. To challenge these theories, we isolated the neutron response from almost any terrestrial changes by operating a bare and a moderated neutron detector in a buoy on a lake in Germany from July 15 to 02 December 2014. We found that the count rate over water has been better predicted by a theory from Köhli et al. (2021, https://doi.org/10.3389/frwa.2020.544847) compared to the traditional approach from Desilets et al. (2010, https://doi.org/10.1029/2009wr008726). We further found strong linear correlation parameters to air pressure (β = 0.0077 mb−1) and air humidity (α = 0.0054 m3/g) for epithermal neutrons, while thermal neutrons responded with α = 0.0023 m3/g. Both approaches, from Rosolem et al. (2013, https://doi.org/10.1175/jhm-d-12-0120.1) and from Köhli et al. (2021, https://doi.org/10.3389/frwa.2020.544847), were similarly able to remove correlations of epithermal neutrons to air humidity. Correction for incoming radiation proved to be necessary for both thermal and epithermal neutrons, for which we tested different neutron monitor stations and correction methods. Here, the approach from Zreda et al. (2012, https://doi.org/10.5194/hess-16-4079-2012) worked best with the Jungfraujoch monitor in Switzerland, while the approach from McJannet and Desilets (2023, https://doi.org/10.1029/2022wr033889) was able to adequately rescale data from more remote neutron monitors. However, no approach was able to sufficiently remove the signal from a major Forbush decrease event on 13 September, to which thermal and epithermal neutrons showed a comparatively strong response. The buoy detector experiment provided a unique data set for empirical testing of traditional and new theories on Cosmic-Ray Neutron Sensing. It could serve as a local alternative to reference data from remote neutron monitors.
Gesehen am 25.11.2024